Alkenylation of cellulose nanocrystals (CNC) and their applications. (28th September 2016) - Miao, Chuanwei; Hamad, Wadood Y.
Abstract: Cellulose nanocrystals (CNC) were modified via surface grafting of (2-Dodecen-1-yl) succinic anhydride (DDSA) in dimethylformamide (DMF). The resulting DDSA-CNC exhibits good dispersibility in organic solvents with a wide range of polarity. In nanocomposite applications, DDSA-CNC can improve both the dispersion of the nanoparticles in the matrix material as well as the interface between them. For a nanocomposite system containing DDSA-CNC with solvent-based polyurethane (PU), 8.3 vol% CNC could increase the maximum tensile strength and Young's modulus by ∼125% and ∼1880%, respectively, and exhibited a 487-fold increase in storage modulus (at 50 °C) relative to neat PU. Our results also indicate there is a significant increase in tensile strength and modulus at fairly low CNC volume fractions (e.g., 2.0 and 4.1 vol%) because of the appreciable interactions between DDSA-CNC and PU through the formation of hydrogen bonding. DDSA-CNC reinforced ethylene propylene diene monomer (EPDM) rubber was also investigated for the first time and the properties characterized. Graphical abstract: Highlights: We report on an effective and facile approach to surface-functionalize cellulose nanocrystals. DDSA-CNC has been prepared through an alkenylation reaction in a suitable solvent. DDSA-CNC has hydrophobic surfaces with significantly higher water contact angles. DDSA-CNC-PU nanocomposites have been prepared via in-situ polymerization. Significant improvement occurs in tensile and DMA at CNC volume fractions >2%.